2018
DOI: 10.1155/2018/6079101
|View full text |Cite
|
Sign up to set email alerts
|

Portulaca Extract Attenuates Development of Dextran Sulfate Sodium Induced Colitis in Mice through Activation of PPARγ

Abstract: Portulaca oleracea L. is a traditional Chinese medicine, which has been used as adjuvant therapy for inflammatory bowel disease (IBD). However, the mechanism of its activity in IBD still remains unclear. Since previous studies have documented the anti-inflammatory effect of peroxisome proliferator activated receptors-γ (PPAR-γ), Portulaca regulation of PPAR-γ in inflammation was examined in current study. Ulcerative colitis (UC) was generated by 5% dextran sulfate sodium (DSS) in mice and four groups were esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
(36 reference statements)
2
25
0
Order By: Relevance
“…6 Previous studies have reported that PPAR-γ could inhibit the expression of NF-κB phosphorylation in cells. 20 In our study, consistent with the report, the expression of PPAR-γ declined in colitis tissue. The proteins of Occludin and ZO-1 are essential for the control of endothelial permeability, the main proteins involved in the tight junction complex.…”
Section: Discussionsupporting
confidence: 93%
“…6 Previous studies have reported that PPAR-γ could inhibit the expression of NF-κB phosphorylation in cells. 20 In our study, consistent with the report, the expression of PPAR-γ declined in colitis tissue. The proteins of Occludin and ZO-1 are essential for the control of endothelial permeability, the main proteins involved in the tight junction complex.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, inhibition of the NF-kB pathway could be an effective target for IBD therapy. In this way, recent studies in DSS-induced colitis mice have shown the ability of natural compounds, such as magnolol, an active ingredient of Magnolia officinalis (Shen et al, 2018), and Portulaca oleracea extract (Kong et al, 2018), from traditional Chinese medicine, to counteract the expression of cytokines, such as TNF-a, IL-1b, and IL-12, via the regulation of NF-kB and PPARg pathways. Another natural compound, Sargahydroquinoic acid isolated from Sargassum incisifolium, and its semisynthetic derivatives have shown agonist activity of PPARg in in vitro assays (Nyambe et al, 2019).…”
Section: Role For Pparg As a Modulator Of Cytokine/chemokine Productionmentioning
confidence: 99%
“…Experimental results demonstrate that the ethanol extract from POL (100, 200 and 400 mg/ kg) treatment increases the colon length, decreases body weight loss and reduces the mRNA expressions of TNFα, IL-1β and IL-6 and the protein expressions of TNF-α and NF-kBp65 in DSS-induced C57BL/6 mice UC model [89]. Additionally, therapeutic effects of portulaca extract (100 mg/kg) is similar to that of mesalazine, which presents reducing the expression levels of these cytokines including TNF-α, IL-6, and IL-1β and the level of DSSinduced NF-κB phosphorylation [90].…”
Section: Detoxificating and Purgative Medicinementioning
confidence: 99%